Potential impact on using aspirin as the primary prevention of adverse pregnancy outcomes in twins conceived using ART - Huang, Dongni; Xie, Yao; Duan, Pingmei; Wang, Jiaxin; Xu, Jiacheng; Qi, Hongbo; Luo, Xin (Scientific reports, 2024)
With the development of assisted reproductive technology, the number of twin pregnancies is increasing year by year. Given the increased risk of pregnancy complications associated with twin pregnancies, and the fact that these babies are rare and difficult to obtain through assisted reproductive technology, clinicians urgently require finding effective and safe drugs to improve pregnancy outcomes. Low-dose aspirin can not only promote placental blood supply, but also effectively anti-inflammatory. Whether Low-dose aspirin can effectively reduce the risk of pregnancy complications in this special group needs to be clarified. We therefore retrospectively analyzed 665 twin pregnancies from assisted reproduction technology, grouped according to aspirin use, and followed pregnancy outcomes to assess bleeding risk. Low-dose aspirin was found to be effective in preventing preeclampsia without a significant risk of bleeding. However, aspirin does not prevent specific complication in twin pregnancies and seems to have a better preventive effect only when the mother is under 30, which should alarm clinicians should not blindly using aspirin in this particular group.